Hubungan Antara Tingkat Pengetahuan Remaja Putri Mengenai Kebersihan Genitalia Eksterna dan Kejadian Keputihan di SMA Negeri 1 Sukodono - Nurmalasari, Lia; , dr. Sri Wahyu Basuki, M.Kes; , dr. Dodik Nursanto (2015)
Background: Fluor albus a reproductive health problems most commonly occur in women. More than 75% of women in the world have experienced fluor albus. Knowledge and care unfavorable external genitalia can lead to problems in the reproductive organs such as fluor albus. The purpose of this study was to determine the relationship between the level of knowledge of the young women about the cleanliness of the external genitalia and the incidence of fluor albus in SMAN 1 Sukodono. Methods: The study is an observational cross-sectional analytic approach. Research subjects were 62 female students in grade 11 in SMAN 1 Sukodono. Sampling was done by simple random sampling. Data collection was performed by administering sheets knowledge questions regarding the cleanliness of the external genitalia and the incidence of fluor albus. The data were analyzed using Chi Square test by SPSS 17:00 for windows. Results: Based on the results, students who are less knowledge and experienced fluor albus were 18 people (58.1%), and who do not experience fluor albus amounted to 9 people (29.0%). While a student with good knowledge and experience fluor albus amounted to 13 people (42.9%), who do not experience fluor albus was 22 people (71.0%). Meanwhile, the p value = 0.021 which means that p <0.05. Thus this analysis has concluded that reject H0. Conclusion: There is a relationship between the level of knowledge of the young women about the cleanliness of the external genitalia and the incidence of fluor albus in SMA 1 Sukodono with p <0.05.